Dampak Partisipasi Masyarakat Dalam Pembangunan Desa Tinigi Kecamatan Galang Kabupaten Tolitoli - Fitri S. Kasim (Formosa Journal of Sustainable Research, 2022)
This study aims to determine the level of community participation in the development of Tinigi Village, Galang District, Tolitoli Regency. This research uses descriptive qualitative. The research informants were 8 people consisting of the village head, village secretary, 1 hamlet head representing the entire hamlet, the head of the PKK, the head of BUMDes, and 3 people from the community. Data analysis techniques used were data collection, data reduction, data presentation and conclusions. From the interview results, firstly, community participation in the form of thoughts, shows that there is a lack of attention from the community as seen from the level of attendance during the village Musrembang, which attended only 45 people out of the total population of 4,550 people. Second, community participation in the form of money, the people in Tinigi Village who cannot participate in development activities because they are hindered by other activities, they will give money to be used by working people, such as buying consumption. Third, community participation in the form of energy, many of the people of Tinigi Village are enthusiastic to participate in village development activities because they are aware that the development was built for the benefit of the people in the village.